Analisis Determinasi Harga Saham Pada Sub Sektor Kosmetik Yang Terdaftar Di Bursa Efek (BEI) Periode 2016-2022 - Tariza Ramadanti; Renea Shinta Aminda; Muhammad Zakie Hanifan (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of Price to Book Value (PBV) and Market Value Added (MVA) on Stock Prices. The population used in this study are companies in the Cosmetics Sub-sector and those listed on the Indonesia Stock Exchange (IDX). The sample selection used the Purposive Sampling method and the companies selected from the criteria were 5 companies for 7 periods, so that the samples used in this study were 35 samples. The data used in this study are secondary data in the form of annual reports and obtained from the Indonesia Stock Exchange. The analysis technique used in this research is regression with panel data and multiple linear regression using the Eviews12 program. The results of this study indicate that Price to Book Value (PBV) has a significant effect on stock prices, Market Value Added (MVA) shows a significant effect on stock prices, Price to Book Value (PBV) and Market Value Added (MVA) have a significant effect on stock prices simultaneously.